Delay of Gratification in Costa Rican Preschoolers: Effect of Trust in the Experimenter and the Socio-Economic Status - Chaverri Chaves, Pablo (2022)
This study analyzed the effect of confidence in the experimenter on the performance of a group of Costa Rican preschoolers on self-control. In addition, the effect of socioeconomic status on performance on the marshmallow task was analyzed by a comparison of children from both different schools (public vs private) and different socioeconomic contexts within each school. The sample of participants was 67 children (26 girls, M of age = 63 months, SD = 6.03). Effects were found, both of the confidence in the experimenter and of the socio-economic status in self-control. The implications of this study for future studies with children and families are discussed. Keywords: Self-control; preschoolers; delay of gratification; candy test; decision making.